Impacts of off-road vehicle tracks on runoff, erosion and sediment delivery – A combined field and modeling approach. (February 2021) - Ramos-Scharrón, Carlos E.
Abstract: Assessing the effects of land disturbance on sediment yield requires quantification of erosion and sediment connectivity. Off-road vehicle (ORV) tracks represent sources of sediment pollution to coral reefs and coastal wetlands in a dry tropical setting of Southwestern Puerto Rico. This study assesses their contribution through a combined empirical and modeling approach. Rainfall simulation experiments and sediment accumulation in detention ponds indicate that ORV track erosion rates are 31–83 Mg ha −1 yr −1 and these are one to two orders of magnitude greater than background erosion rates. A new sediment connectivity model predicted a watershed-scale sediment yield of 2.7 Mg ha −1 yr −1 from a 11.9 km km −2 of ORV track network, and this exceeds those from comparable watersheds in the Caribbean. The spatially explicit nature of the model outputs allows for site-specific quantification of sediment contributions and for an evaluation of the effectiveness of mitigation methods such as detention ponds. Highlights: ORV tracks represent sources of sediment pollution to coral reefs in a dry tropical setting of southwest Puerto Rico. ORV track erosion rates are one to two orders of magnitude greater than background rates. Predicted sediment yields due to ORV tracks exceed those from other comparable watersheds in the Caribbean. Model outputs allow for site-specific sediment delivery estimates and evaluation of reductions due to detention ponds.